Strengthening Law On Cultural And Religious Rights In The New Normal Era - Rafli Yoga Ramadhan; Thoriq Izhar Azhari; Jan Alizea Sybelle (Universitas Muhammadiyah Surakarta, 2022)
This study aims to examine diversity in Indonesia with the existence of legal products such as laws using the perspective of F. Budi Hardiman, namely the concept of transformational justice. Diversity in Indonesia indicates that Indonesia has a pre-political view that is not only a matter of fingers, so the related dilemma is also about the trap of the concept of justice between the calendar of cultural identity or the loss of the political concept of the state due to the domination of a group so that the system of action has an important role in it. This research uses interviews and documentation studies to collect legal products and explores the nature of diversity in Indonesia. The results show that in Indonesia, legal products are indeed a system of action that transforms diversity into a systemic realm. it' s just that there needs to be further socialization so that there is no bias in the concept of multiethnic justice by freezing on liberalism, communitarianism and multiculturalism. Finally, this research can be useful for the field of law, especially the sociology of law. Sustainable development is very dependent on human resources so how the concept of Human Rights is interpreted in the new normal era is the key to the answer that determines the continuity of sustainable development in Indonesia. The principle of proportionality should be the basis for logical thinking in guaranteeing and enforcing human rights in the new normal era in order to maintain the sustainability of sustainable development. The author is of the opinion that for this reason, human rights, both civil and political rights, and economic and social rights,